Diversity of flowering plants of Gautala Autramghat reserved forest in Marathwada (M.S.) India - A, Gitte T; Kare, M A; Deshmukh, A M (Recent Research in Science and Technology, 2012)
Present study deals with the diversity of Gautala autramghat reserved forest in Marathwada. In order to understand the present status of flowering plants of the area, a survey has been carried out about two years. The main dominant components covering the area are Tectona grandis L.f., Terminalia arjuna W. & A., Dalbergia sissoo Roxb. ex DC., Zizipus mauritiana Lamk., Butea monosperma (Lamk.) Taub.